Synthesis, In Silico and Pharmacological Evaluation of New Thiazolidine-4-Carboxylic Acid Derivatives Against Ethanol-Induced Neurodegeneration and Memory Impairment - Naz S; Al Kury LT; Nadeem H; Shah FA; Ullah A; Paracha RZ; Imran M; Li S (Dove Medical Press, 2022)
Shagufta Naz,1,2 Lina Tariq Al Kury,3 Humaira Nadeem,1 Fawad Ali Shah,1 Aman Ullah,1 Rehan Zafar Paracha,4 Muhammad Imran,5 Shupeng Li2 1Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, 44000, Pakistan; 2State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Peking University, Shenzhen, People's Republic of China; 3College of Natural and Health Sciences, Zayed University, Abu Dhabi, 49153, United Arab Emirates; 4Research Center for Modeling & Simulation (RCMS), National University of Sciences and Technology (NUST), Islamabad, 44000, Pakistan; 5Department of Pharmacy, IQRA University, Islamabad, 44000, PakistanCorrespondence: Humaira Nadeem, Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, 44000, Pakistan, Tel +92 51-2891835, Fax +92 51-8350180, Email humaira.nadeem@riphah.edu.pk Shupeng Li, State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Peking University, Shenzhen, People's Republic of China, Email lisp@pku.edu.cnIntroduction: Several studies revealed that alcohol utilization impairs memory in adults; however, the underlying mechanism is still unclear. The production of inflammatory markers and reactive oxygen species (ROS) plays a major role in neurodegeneration, which leads to memory impairment. Therefore, targeting neuroinflammation and oxidative distress could be a useful strategy for abrogating the hallmarks of ethanol-induced neurodegeneration. Moreover, several studies have demonstrated multiple biological activities of thiazolidine derivatives including neuroprotection.Methods: In the current study, we synthesized ten (10) new thiazolidine-4-carboxylic acid derivatives (P1-P10), characterized their synthetic properties using proton nuclear magnetic resonance (1H-NMR) and carbon-13 NMR, and further investigated the neuroprotective potential of these compounds in an ethanol-induced neuroinflammation model.Results: Our results suggested altered levels of antioxidant enzymes associated with an elevated level of tumor necrosis factor-alpha (TNF-α), nuclear factor-κB (p-NF-κB), pyrin domain-containing protein 3 (NLRP3), and cyclooxygenase-2 (COX-2) in ethanol-treated animals. Ethanol treatment also led to memory impairment in rats, as assessed by behavioral tests. To further support our notion, we performed molecular docking studies, and all synthetic compounds exhibited a good binding affinity with a fair bond formation with selected targets (NF-κB, TLR4, NLRP3, and COX-2).Discussion: Overall, our results revealed that these derivatives may be beneficial in reducing neuroinflammation by acting on different stages of inflammation. Moreover, P8 and P9 treatment attenuated the neuroinflammation, oxidative stress, and memory impairment caused by ethanol.Graphical Abstract: Keywords: thiazolidine, oxidative stress, neuroinflammation, neuroprotective, molecular docking, ethanol